1D Models for Enzymatic Biological Fuel Cells. (January 2015) - Calabrese Barton, Scott
Abstract : Enzyme electrocatalysts offer a unique approach to fuel cell system design by broadening the range of fuel and oxidants available expanding the library of low cost organic and transition metal catalysts. Increased understanding of redox enzymes will further our ability to design catalyst active sites and possibly lead to breakthroughs in enzyme electrocatalytic technology. The design and analysis of bioelectrocatalytic systems, not only for fuel cells but also for biosensor and bioconversion applications, requires detailed quantitative understanding of the physicochemical phenomena controlling such systems (kinetics, mass transport etc.). Similarly, building real-world systems with bioelectrocatalysts requires engineering approaches to predict the effect of length scales on device performance. This article describes some modeling approaches for enzymatic fuel cells that are applicable to many other systems, including biosensors and bioreactors, with some emphasis on recent advances. We discuss basic thin film 1D models and their analytical and numerical solutions, and then introduce the treatment of porous bioelectrodes, which covers the vast majority of practical devices. Finally we describe one type of complete cell model.